Moderate Knowledge and Attitudes Toward Tonsillitis Among Nursing Students - Husham Hussain Abdul-Ra’aoof; Wedad Amer Mizher; Ali Malik Tiryag; Mohammed M.J. Al-khalissi; Tabarek Mohammed Neama; Nabaa Hassan Nayef (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Tonsillitis, a common pediatric illness, is typically self-limiting and primarily viral in origin, though bacterial forms—especially those caused by group A streptococcus—can result in serious complications. Specific Background: Nursing students, as future frontline healthcare providers, require foundational understanding and attitudes toward pediatric infections like tonsillitis to promote effective patient education and clinical decision-making. Knowledge Gap: Limited studies have assessed the adequacy of nursing students’ knowledge and attitudes regarding tonsillitis in children, particularly in Middle Eastern academic contexts. Aim: This study aimed to evaluate the knowledge and attitudes of nursing students at the University of Basrah regarding pediatric tonsillitis. Results: Among 150 students surveyed, most demonstrated moderate knowledge and attitudes toward the condition, with significant gaps in understanding its infectious nature and complications. Novelty: This study highlights underexplored misconceptions among nursing students—such as low awareness of the infectious potential and complications of tonsillitis—despite relatively high awareness of its immunological and symptomatic aspects. Implications: Targeted educational interventions are necessary to address specific knowledge deficiencies and reinforce accurate clinical perspectives, thereby improving early detection, appropriate referral, and rational antibiotic use in pediatric tonsillitis care. HIghlight : Moderate Understanding: Most nursing students demonstrated moderate knowledge and attitudes regarding tonsillitis in children. Gender Distribution: A higher percentage of female students (66%) participated compared to males (34%). Misconceptions Noted: Only 17.3% correctly identified tonsillitis as infectious, highlighting a crucial gap in understanding. Keywords: Knowledge, Attitude, Tonsillitis, Children, Nursing Students